Misi dalam Tantangan Zaman: Sebuah Analisa Perjalanan Misi Kaum Pentakosta di Indonesia - David Folind Zega; Febe Simatupang; Agiana Her Visnhu Ditakristi (Sabda: Jurnal Teologi Kristen, 2025)
The church's role in fulfilling God's mission is a primary calling for all people across religions and cultures. However, many churches today have begun to lose their zeal in responding to the Great Commission entrusted by God. In this modern era of rapid technological development, some churches in Indonesia tend to focus more on internal matters. This condition poses a serious challenge that may hinder the fulfillment of God's mission. Ironically, technological advancements have not been maximized to expand the scope of mission work. This article aims to identify the challenges faced by Pentecostal churches in Indonesia in the context of modern society and highlight the role of the Holy Spirit in awakening missional awareness among churches and God’s servants. Using a qualitative approach, this study encourages churches to actively respond to contemporary challenges while remaining faithful to their divine mission in a relevant and contextual manner. Abstrak:Peran gereja dalam misi Allah merupakan panggilan utama bagi seluruh umat manusia lintas agama dan budaya. Namun, banyak gereja mulai kehilangan semangat dalam menanggapi Amanat Agung yang Tuhan percayakan. Di era modern yang ditandai oleh pesatnya perkembangan teknologi, sebagian gereja di Indonesia justru lebih fokus pada urusan internal. Kondisi ini menjadi tantangan serius yang dapat menghambat pelaksanaan misi Allah. Ironisnya, kemajuan teknologi belum dimanfaatkan secara maksimal untuk memperluas pelayanan misi. Artikel ini bertujuan mengidentifikasi tantangan yang dihadapi gereja Pentakostal dalam konteks zaman modern serta menyoroti peran Roh Kudus dalam membangkitkan kesadaran misi di kalangan gereja dan hamba Tuhan. Dengan pendekatan kualitatif, tulisan ini diharapkan mendorong gereja untuk aktif menjawab tantangan zaman dan tetap setia pada panggilan misinya secara relevan dan kontekstual. Kata Kunci: Era Modern, Pelayanan Misi Pentakosta, Tantangan.